A pilot study of Merkel cell polyomavirus in squamous cell carcinoma of the tongue. (November 2017) - Hamiter, Mickie; Asarkar, Ameya; Rogers, Donna; Moore-Medlin, Tara; McClure, Gloria; Ma, Xiaohui; Vanchiere, John; Nathan, Cherie-Ann O.
Highlights: A significant association between oral tongue squamous cell carcinoma (SCC) and Merkel cell polyoma virus is reported. The presence of MCPyV virus in oral tongue SCC was associated with lower recurrence rates. Although a causal relationship is not suggested by this study, findings are novel and interesting to test this hypothesis.